PELANGGARAN MAKSIM DALAM PODCAST “PURBAYA YUDHI SADEWA (KETUA DEWAN KOMISIONER LPS): LPS DISERANG 3 M HACKER?” - Elva Meilani Sagita; sonya Trikandi; Hugo Dimas Ohsyahida; Pramudita Arjuna AP; Tiara (Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study investigates psycholinguistic aspects related to human thought processes in understanding and producing language by analyzing maxim violations in the CXO Media podcast featuring Purbaya Yudhi Sadewa (Chairman of the LPS Board of Commissioners). By applying pragmatic qualitative methods and a descriptive approach, this study aims to reveal how spontaneous communication strategies in oral conversations can deviate from the Cooperative Principle proposed by Grice. The results of the analysis revealed 7 (seven) findings of maxim violations including, 4 (four) violations of the maxim of quality, characterized by exaggeration and simplification of facts without sufficient evidence, 2 (two) violations of the maxim of quantity due to providing unclear and inconsistent information, and 1 (one) violation of the maxim of manner involving the use of unclear, repetitive, and wordy language. Overall, these findings indicate that maxim violations in the context of sensitive issues such as customer fund security and cyber attacks act as psychological tools to convince the public, build a positive image, and provide a sense of security to listeners through persuasive delivery.